Antiinflammatory effects of reconstituted high-density lipoprotein during human endotoxemia - Pajkrt, D; Doran, J E; Koster, F; Lerch, P G; Arnet, B; van der Poll, T; ten Cate, J W; van Deventer, S J (The Journal of experimental medicine, 1996)
High-density lipoprotein (HDL) has been found to neutralize LPS activity in vitro and in animals in vivo. We sought to determine the effects of reconstituted HDL (rHDL) on LPS responsiveness in humans in a double-blind, randomized, placebo-controlled, cross-over study. rHDL, given as a 4-h infusion at 40 mg/kg starting 3.5 h before endotoxin challenge (4 ng/kg), reduced flu-like symptoms during endotoxemia, but did not influence the febrile response. rHDL potently reduced the endotoxin-induced release of TNF, IL-6, and IL-8, while only modestly attenuating the secretion of proinflammatory cytokine inhibitors IL-1ra, soluble TNF receptors and IL-10. In addition, rHDL attenuated LPS-induced changes in leukocyte counts and the enhanced expression of CD11b/CD18 on granulocytes. Importantly, rHDL infusion per se, before LPS administration, was associated with a downregulation of CD14, the main LPS receptor, on monocytes. This effect was biologically relevant, since monocytes isolated from rHDL-treated whole blood showed reduced expression of CD14 and diminished TNF production upon stimulation with LPS. These results suggest that rHDL may inhibit LPS effects in humans in vivo not only by binding and neutralizing LPS but also by reducing CD14 expression on monocytes.